Selective ROCK Inhibitor Enhances Blood Flow Recovery after Hindlimb Ischemia - Hend Salah Fayed (17732622) (2023)
The impairment in microvascular network formation could delay the restoration of blood flow after acute limb ischemia. A high-content screen of a GSK-published kinase inhibitor library identified a set of ROCK inhibitor hits enhancing endothelial network formation. Subsequent kinase activity profiling against a panel of 224 protein kinases showed that two indazole-based ROCK inhibitor hits exhibited high selectivity for ROCK1 and ROCK2 isoforms compared to other ROCK inhibitors. One of the chemical entities, GSK429286, was selected for follow-up studies. We found that GSK429286 was ten times more potent in enhancing endothelial tube formation than Fasudil, a classic ROCK inhibitor. ROCK1 inhibition by RNAi phenocopied the angiogenic phenotype of the GSK429286 compound. Using an organotypic angiogenesis co-culture assay, we showed that GSK429286 formed a dense vascular network with thicker endothelial tubes. Next, mice received either vehicle or GSK429286 (10 mg/kg i.p.) for seven days after hindlimb ischemia induction. As assessed by laser speckle contrast imaging, GSK429286 potentiated blood flow recovery after ischemia induction. At the histological level, we found that GSK429286 significantly increased the size of new microvessels in the regenerating areas of ischemic muscles compared with vehicle-treated ones. Our findings reveal that selective ROCK inhibitors have in vitro pro-angiogenic properties and therapeutic potential to restore blood flow in limb ischemia. Other Information Published in: International Journal of Molecular Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijms241914410